Motion behavior of droplets on curved leaf surfaces driven by airflow - Gao, Zhou-Ming; Hu, Wei; Dong, Xiao-Ya; Zhao, Xiao-Yuan; Wang, Song; Chen, Jian; Qiu, Bai-Jing (Frontiers in Plant Science, 2024)
Airflow-assisted spray technology enhances pesticide application efficiency and coverage uniformity. However, insufficient wind speed can prevent droplets from penetrating the plant canopy, while excessive wind speed can blow away droplets deposited on leaves, reducing pesticide effectiveness. This study utilizes wind tunnels and high-speed camera systems to observe the motion behavior of droplets on curved leaf surfaces. The results indicate that the curvature of leaves during bending deformation is mostly less than 0.05 mm -1 . The critical wind speed of droplets is negatively correlated with particle size and leaf curvature. The critical wind speed difference of droplets on different curved leaves is 24.8%, and the maximum difference in critical wind speed for droplets of different particle sizes is 17.5%. During droplet movement, the droplet dimensionless shape variable is positively correlated with particle size and leaf curvature. Within the test duration, the maximum dimensionless shape variable on various curved leaves reaches 0.24, and the acceleration can differ by about 30%. For droplets of different sizes, the maximum dimensionless shape variable is 0.18, the acceleration can differ by about 68%. These findings contribute to a deeper understanding of droplet-leaf interactions and provide valuable insights for improving pesticide efficacy.